Infrastructures for disorder. Applying Sennett's notion of disorder to the public space of social housing neighbourhoods. Issue 3 (3rd May 2016) - Sendra, Pablo
Abstract: This paper contributes to the debate on whether introducing too much order into urban regeneration processes hinders social life and interaction in the public space. It engages with Sennett's call for introducing certain kinds of disorder into city life. While this debate has been addressed in urban literature, many urban regeneration processes in social housing neighbourhoods have attempted to remove all kinds of disorder from the city, thus removing urban life from the streets. This paper proposes 'infrastructures for disorder': strategies for intervention that create conditions for the unplanned use of the public realm in social housing estates.